Has It Come to This? 2020
DOI: 10.36019/9781978809390-014
|View full text |Cite
|
Sign up to set email alerts
|

14 Promises of Climate Engineering after Neoliberalism

Abstract: The apparent, if uncertain, rejection of neoliberalism manifested by the election of Donald Trump in the US (alongside the slim, but clear majority for Brexit in the UK, and a growing racist and protectionist nationalism across Europe) necessitates renewed analysis of the future of both promises of technical fixes to climate change, such as carbon capture and storage (CCS), carbon dioxide removal (CDR) and solar radiation management (SRM) (in this chapter collectively referred to as climate engineering), and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…We then also discuss how the practices of the cultural political economy of mitigation deterrence co-evolve. For this, we build on McLaren and Markusson [ 32 ] who reviewed the history of low-carbon technology promises, and their co-evolution with modelling and climate policy, and showed that NETs is only one in a series of technology promises that have undermined climate action. Finally, we briefly speculate on how these practices might fare under a change away from the current neoliberal political regime.…”
Section: Digging a Hole: Co-evolving Practices Of The Cultural Politi...mentioning
confidence: 99%
See 2 more Smart Citations
“…We then also discuss how the practices of the cultural political economy of mitigation deterrence co-evolve. For this, we build on McLaren and Markusson [ 32 ] who reviewed the history of low-carbon technology promises, and their co-evolution with modelling and climate policy, and showed that NETs is only one in a series of technology promises that have undermined climate action. Finally, we briefly speculate on how these practices might fare under a change away from the current neoliberal political regime.…”
Section: Digging a Hole: Co-evolving Practices Of The Cultural Politi...mentioning
confidence: 99%
“…An analysis of the history of climate science and policy shows that mitigation deterrence has had many previous manifestations, and is not just an issue for NETs. McLaren and Markusson [ 32 ] mapped the history of climate policy in five phases, and related this to developments in modelling and the prominence of a range of technology promises, drawing mainly on international and UK material. Each phase has two distinct characteristics: a change in conceptualisation of the overarching goal of avoiding dangerous climate change, or ‘target framing’; and shifting promises of future technology deployment.…”
Section: Digging a Hole: Co-evolving Practices Of The Cultural Politi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, as we show below, fossil fuel interests and climate denial organizations are now largely absent from SG policy-planning, while prominent criticism of the technology continues to link it to the fossil fuel industry (ETC Group et al 2017;Schneider & Fuhr 2020;Muffett & Feit 2019). These critiques are well-founded, as SAI logically serves the interests of the fossil fuel industry in its promise to extend fossil capitalism (Gunderson et al 2019;Markusson et al 2020). However, they tend to overlook many of the more subtle ways the technology has advanced and is now promoted by climate scientists, environmental NGOs, 'green' philanthropists, and Silicon Valley ecomodernists -the 'climate capitalist' policy network (Newell & Paterson 2010;Sapinski 2015Sapinski , 2016.…”
Section: Introductionmentioning
confidence: 99%